Alpha and beta type 1 interferon signaling: passage for diverse biologic outcomes - Ng, Cherie T. (Cell, 2016)
Type I interferon (IFN-I) elicits a complex cascade of events in response to microbial infection. Here, we review recent developments illuminating the large number of IFN-I species and describing their unique biologic functions.